Effect of thermal radiation on a three-dimensional stagnation point region in nanofluid under microgravity environment - Kamal, M. H. A. (Horizon Research Publishing, 2019)
The unsteady three dimensional boundary layer flow near a stagnation point region is studied numerically under the influence of microgravity environment. The boundary layer plate was embedded by the nanofluid with nanosized copper particles and water as a based fluid together with thermal radiation effect. The problem was mathematically formulated in term of coupled governing equations consisting of continuity, momentum and energy equations derived from the fundamental physical principles with Tiwari and Das nanofluid model. Boundary layer and Boussinesq approximation were then applied to the coupled equations and then reduced into non-dimensional equations to lessen the complexity of the problem using semi-similar transformation technique. Implicit finite different method known as Keller box method was used in this problem. The problem was then analyzed in terms of physical quantities of principal interest known as skin frictions and Nusselt number which explained the flow behavior and heat transfer analysis. From the outcome of the analysis, it was found that the parameter values for curvature ratio lead to the different cases of the stagnation point flow which is either plane stagnation flow or asymmetry stagnation flow. On the other hand, by increasing the nanoparticles volume fraction which is one of the nanofluid parameter may increase the skin frictions on both x- and y-directions. The presence of thermal radiation parameter was found to have increased the rate of change of heat transfer at the boundary layer flow.